A quickly accessed method for I2RS in open-source router - Quan SHI; Dejing LIU (Dianxin kexue)
Southbound interface protocol specification I2RS（interface to routing system）appears in the transitional period of traditional network to SDN（software defined networking）.Based on the protocol specification,a method which could get the state and statistics information of network's equipments in a more efficient way was put forward.The design was detailed and adequately testing was performed,which included the speed of getting information about equipments' state and statistics,the numbers of the wrong information as well as the recovery time from exception.The experiment results show that the proposed method improves the speed of getting the information about equipments' state and statistics,which is better than the existed method and when some exceptions happen,the proposed method can recover the situation quickly.The application of the real network environment shows that the proposed method can get the wanted information quickly and stably.